Crowding and Queuing in Entrance Scenarios: Influence of Corridor Width in Front of Bottlenecks - Adrian, Juliane; Boltes, Maik; Holl, Stefan; Sieben, Anna; Seyfried, Armin (Collective Dynamics, 2020)
In this paper, we present results of an entrance experiment investigating the effect of the corridor width in front of a bottleneck on the density. The idea is based on a previous study suggesting that a guiding system in front of an entrance can reduce pushing of the waiting people and thus the density at the entrance. In our study we aim to find out to what extend the corridor width has an impact on crowding or queuing behavior and with that on the density. The results of the presented experiment suggest that the transition takes place between a corridor width of 1.2 m and 2.3 m. The total duration of each experimental run is not significantly influenced by the corridor width but by the width of the entrance itself, the number of participants and partly by the motivation. In general, the density in front of the gate as well as the area of high density is increased by widening the corridor and by intensifying the motivation of the participants. However, the results also suggest that also the number of participants significantly influences the occurrence of pushing and the level of density.